3^x + 4^y equals 5^z has Unique Solution
Theorem
The Diophantine equation:
- $3^x + 4^y = 5^z$
has exactly one solution in (strictly) positive integers:
- $3^2 + 4^2 = 5^2$
Proof
Rewriting our Diophantine equation modulo $4$ we have:
- $\paren {-1}^x + 0^y \equiv 1^z \pmod 4$
Therefore $x$ is even.
Rewriting our Diophantine equation modulo 3 we have:
- $0^x + 1^y \equiv \paren {-1}^z \pmod 3$
Therefore $z$ is even.
Since $x$ and $z$ must both be even, we will rewrite $x$ as $2 r$, $z$ as $2 s$ and notice that $4$ is $2^2$.
We now have:
\(\ds 3^{2 r} + 2^{2 y}\) | \(=\) | \(\ds 5^{2 s}\) | ||||||||||||
\(\ds 5^{2 s} - 3^{2 r}\) | \(=\) | \(\ds 2^{2 y}\) | rewriting the equation | |||||||||||
\(\ds \paren {5^s + 3^r} \paren {5^s - 3^r}\) | \(=\) | \(\ds 2^{2 y}\) | factoring the left hand side: Difference of Two Squares |
We can see that the right hand side is a product consisting entirely of instances of $2$.
Therefore:
- $\paren {5^s + 3^r} = 2^u$
and:
- $\paren {5^s - 3^r} = 2^v$
where $u > v$ and $u + v = 2 y$.
Solving for $5^s$, we add the two equations and get:
\(\ds \paren {5^s + 3^r} + \paren {5^s - 3^r}\) | \(=\) | \(\ds 2^u + 2^v\) | ||||||||||||
\(\ds 5^s\) | \(=\) | \(\ds 2^{u - 1} + 2^{v - 1}\) | Dividing both sides by $2$ | |||||||||||
\(\ds \) | \(=\) | \(\ds 2^{v - 1} \paren {2^{u - v} + 1}\) | Factoring out $2^{v - 1}$ |
Solving for $3^r$, we subtract the two equations and get:
\(\ds \paren {5^s + 3^r} - \paren {5^s - 3^r}\) | \(=\) | \(\ds 2^u - 2^v\) | ||||||||||||
\(\ds 3^r\) | \(=\) | \(\ds 2^{u - 1} - 2^{v - 1}\) | dividing both sides by $2$ | |||||||||||
\(\ds \) | \(=\) | \(\ds 2^{v - 1} \paren {2^{u - v} - 1}\) | factoring out $2^{v - 1}$ |
Since both $5^s$ and $3^r$ are odd, $v$ must be equal to $1$.
Let $t = u - v$.
We now have:
- $5^s = \paren {2^t + 1}$
- $3^r = \paren {2^t - 1}$
Let us now consider the second equation Modulo 3:
- $0 \equiv \paren{-1}^t - 1 \pmod 3$
Therefore t must be even.
We will rewrite the second equation above with $t$ as $2 w$:
\(\ds 3^r\) | \(=\) | \(\ds \paren {2^{2w} - 1}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \paren {2^w + 1} \paren {2^w - 1}\) | Difference of Two Squares |
We can see that the left hand side is a product consisting entirely of instances of $3$.
Therefore:
- $ 3^m = \paren {2^w + 1}$
and:
- $ 3^n = \paren {2^w - 1}$
where $m > n$ and $m + n = r$.
Subtracting the $2$ equations above we get:
\(\ds 3^m - 3^n\) | \(=\) | \(\ds \paren{2^w + 1} - \paren{2^w - 1}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds 2\) |
Therefore $m = 1$ and $n = 0$.
From above:
- $3^m = \paren {2^w + 1}$
therefore:
- $w = 1$
Recall that $t = 2w$.
Therefore:
- $t = 2$
and:
- $5^s = \paren {2^t + 1}$
- $3^r = \paren {2^t - 1}$
Therefore $r = 1$ and $s = 1$.
Finally recall that $x = 2 r$ and $z = 2 s$.
Therefore we arrive at the only possible solution in (strictly) positive integers:
- $x = 2$, $y = 2$ and $z = 2$
$\blacksquare$
Sources
- 1993: Nobuhiro Terai: The Diophantine equation $x^2 + q^m = p^n$ (Acta Arithmetica Vol. 63: pp. 351 – 358)
- 1997: David Wells: Curious and Interesting Numbers (2nd ed.) ... (previous) ... (next): $2$